2018
DOI: 10.1007/s00394-018-1606-4
|View full text |Cite
|
Sign up to set email alerts
|

Postoperative intermittent fasting prevents hippocampal oxidative stress and memory deficits in a rat model of chronic cerebral hypoperfusion

Abstract: Our results suggest that postoperative IF suppresses neuroinflammation and oxidative stress induced by chronic cerebral ischemia, thereby preserving cognitive function in a vascular dementia rat model.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
24
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(28 citation statements)
references
References 25 publications
1
24
0
3
Order By: Relevance
“…Nutrients 2020, 12, 1029; doi:10.3390/nu12041029 www.mdpi.com/journal/nutrients a reduction in blood pressure and heart rate [16][17][18][19][20]; a reduction in inflammation; and protection against neurodegeneration [17][18][19][21][22][23][24][25][26][27][28][29][30].…”
Section: Introductionmentioning
confidence: 99%
“…Nutrients 2020, 12, 1029; doi:10.3390/nu12041029 www.mdpi.com/journal/nutrients a reduction in blood pressure and heart rate [16][17][18][19][20]; a reduction in inflammation; and protection against neurodegeneration [17][18][19][21][22][23][24][25][26][27][28][29][30].…”
Section: Introductionmentioning
confidence: 99%
“…However, in the same study 30–40% CR increased GSH level in rats liver tissue compared to the AL‐fed groups . Similarly, effects of intermittent fasting on increasing GSH level in hippocampus tissue of 18‐week‐old male rats subjected to 24‐hour food deprivation every other day for 7 weeks were also reported . Moreover, compared to AL group, increased GSH level in liver tissue was reported in 8‐week‐old male rats following every other day fasting for 4 weeks.…”
Section: Discussionmentioning
confidence: 69%
“…For example, when eight‐week‐old male rats were fed every other day (alternative day fasting) for 1 month, lower MDA level was measured compared to controls in heart tissue of fasting group while no difference was reported in brain, muscle, and liver tissues . In another study, lower level of MDA was also measured in hippocampus of 18‐week‐old male rats that were deprived of food for 24 hr every other day for 7 weeks . Moreover, in human studies, a 54.3% decrease in serum MDA levels was measured in people who fasted from sunrise to sunset during Ramadan for 1 month.…”
Section: Discussionmentioning
confidence: 97%
“…Furthermore, Arumugam et al (2010) showed that IF increased the HO-1 level in vulnerable brain regions, and the increased HO-1 level was correlated with decreasing infarct volume and neurological deficit following focal cerebral ischemic stroke in mice ( 26 ). Recently, Hu et al (2017) reported that postoperative IF for a week after chronic cerebral hypoperfusion in rats significantly decreased malondialdehyde (MDA) activity, maintained glutathione, SOD1, and SOD2 levels in the hippocampus, and improved memory deficit induced by the hypoperfusion ( 30 ). In our present study, we found that SOD2 and CAT immunoreactivities were hardly shown in CA pyramidal cells in the IF+Ischemia group; instead, the immunoreactivities were increased in non-pyramidal cells, which were found to be astrocytes ( 31 , 32 ), compared to the Ischemia group.…”
Section: Discussionmentioning
confidence: 99%